Implementasi Budaya Komunikasi Organisasi Berbasis Kearifan Lokal Pasang Ri Kajang pada Pemerintah Kabupaten Bulukumba - Emil Fatra; Thiara Tri Funni Manguma; Rusli (FKIP - Universitas Pahlawan Tuanku Tambusai, 2026)
Pasang Ri Kajang local wisdom serves as the guiding philosophy of life for the Kajang indigenous community (Keammatoaan) and has been adopted by the Government of Bulukumba Regency as the foundation of its organizational communication culture. This study aims to identify the forms of organizational communication culture categorization and examine the implementation of an organizational communication culture based on the local wisdom of Pasang Ri Kajang within the Government of Bulukumba Regency. The study employed a qualitative descriptive method using a communication ethnography approach. Data were collected through observation, in-depth interviews, and documentation. The findings reveal four main categories of organizational communication culture implemented within the Bulukumba Regency Government. These include the principle of Lambusu na Gattang, which emphasizes honesty, adherence to rules, and discipline; Palampa Paunnu, which promotes openness, particularly in information dissemination and the management of development programs; Assipakatau, which fosters harmony and mutual respect among employees; and Sipatuntung, which encourages mutual support, motivation, and synergy among organizational members. Furthermore, the study found that the implementation of an organizational communication culture based on Pasang Ri Kajang local wisdom is manifested through several practices, including the organization of an annual cultural festival featuring participants dressed in traditional black attire, the application of the Tallasa Kamase-masea principle, which emphasizes simplicity and self-restraint, the Allemo Si Batu principle, which promotes unity and the preservation of cultural values, and the practice of Siri', a cultural value emphasizing shame, self-awareness, and moral responsibility to avoid actions that may harm society.